Traditional Applications, Phytochemistry, and Pharmacological Activities of Eupatorium lindleyanum DC.: A Comprehensive Review - Wang, Xueyi; Ma, Shangying; Lai, Feifan; Wang, Yiqi; Lou, Chenghua (Frontiers in Pharmacology, 2020)
Eupatorium lindleyanum DC. (EL) has a long history of traditional use in China to cure coughs, chronic bronchitis, lobar pneumonia and hypertension. Because of this extensive use of EL in traditional medicine, this present review gives a systematic overview of the conventional applications, phytochemistry and pharmacological effects of the herb. Literature was systematically searched using the scientific databases ScienceDirect, SciFinder, CNKI, Wiley, Baidu Scholar, SpringerLink, PubMed, Web of Science, and other professional websites. Information was also gathered from books on traditional Chinese herbal medicine, the Chinese Pharmacopoeia and Chinese Materia Medica. To date, many preparations of EL have been widely used clinically to treat various diseases of the respiratory system. Over 100 compounds have been isolated from the herb, including triterpenes, sesquiterpenes, sesquiterpene lactones, flavonoids, acyclic diterpenoids, sterols, and so on. Among them, terpenoids are considered to be the most important bioactive substances in EL. The pharmacological functions of EL, including anti-asthmatic, anti-tussive, anti-inflammatory, anti-hyperlipidemic, anti-hypertensive, anti-virus and anti-tumor activities, have been widely investigated. However, most of the studies are preclinical research. Further studies are required to examine the underlying mechanisms of action. Traditionally, EL is used for treating many diseases, especially respiratory diseases. Unfortunately, up to now, modern studies have not yet well elucidated the conventional usage of EL. Most importantly, its biological activities and the corresponding constituents are still unclear. Moreover, studies on the pharmacokinetics and toxicity of EL are few, so data on the clinical safety of EL is lacking. Taken together, research work on EL is quite preliminary. More in-depth studies of phytochemistry, pharmacological activities, pharmacokinetics and toxicity of the herb, are needed. This review aims to provide valuable information on EL to guide future investigations and applications.